Simulation Study on Cooling and Ventilation Effect of Different Central Air Collection Pipe Forms on Shallow Circular Warehouse - YANG Tai; ZHANG Xiu-lin; SUN Hao-sen; WANG Yuan-cheng; YANG Kai-min (Liang you shipin ke-ji, 2022)
On the basis of CFD numerical simulation technology, the numerical simulation results of radial ventilation and cooling under different central air collection pipe forms of shallow circular silo were analyzed, and they were compared to judge the advantages and disadvantages. The grain type studied in this paper was soybean. The temperature distribution and air distribution in the grain pile under the ventilation of the top or opening or non-circulation of four variable diameter central air collection pipes were numerically simulated. The numerical simulation results of the eight cases were compared to analyze their ventilation uniformity and ventilation cooling rate. It is found that the air collecting duct has obvious advantages when its height was flush with the grain surface, thick at the top and fine at the bottom, which is mainly reflected in its ventilation uniformity. The research results provide theoretical guidance and basis for the selection of ventilation and cooling methods for soybean storage in shallow circular warehouse.